The Future of Indonesia Islamic Banking Industry: Bankruptcy Analyzing the Second Wave of Global Financial Crisis - Patria Yunita (International Journal of Islamic Economics and Finance (IJIEF), 2020)
This study aims to analyze the resilience of the Indonesia Islamic banking industry from bankruptcy risk in times of financial crisis. This study use binary regression as dependent variable. The Islamic banking industry bankruptcy risk generated from capital buffering changes in accordance with POJK No. 11 / POJK.03 / 2016. Economic Growth, BI rate, Inflation rate and Islamic Money Market O/N rate as independent variables. To anticipate the unobserved heterogeneity, Bank Profitability, USD Exchange Rate, Federal Reserves Interest Rate and  Money Supply (M2) are used as control variables. Data analysis to predict bankruptcy uses logistic regression model of the global financial crisis in Indonesia. Data obtained from monthly statistics report of Bank Indonesia and the Financial Services Authority from Januari 2008 until December 2019 by the structural break which impacted the Islamic banking capital on December 2012.  Our analysis divide indonesia financial condition into two difference time, before and after the structural break. By Probit Logit Regression Model, it was concluded that USD exchange rate is independent variable which is consistently influence the probability of islamic banking bankruptcy risks in all period. BI rate not significantly affected the probability of Islamic banking bankruptcy because profit and loss sharing method applied in Islamic banking. Before the structural break the probability of bankruptcy  significantly affected by Money Supply, USD exchange rate and economic growth. But after the structural break, the probability of bankruptcy significantly affected by Bank Profitability, USD exchange rate, BI rate and Islamic Money Market rate. This model precisely predicted by Count R Squared of 75.81% - 86.67%.